RESPONSE OF DIFFERENT BODY WEIGHTS ON BLOOD SERUM CHEMISTRY VALUES IN FOUR CLOSE-BRED FLOCKS OF ADULT JAPANESE QUAILS (Coturnix coturnix japonica) - A. S. Jatoi; A. W. Sahota; M. Akram; K. Javed; J. Hussain; S. Mehmood; M. H. Jaspal (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to investigate blood serum chemistry values in four close-bred flocks of adult Japanese quails responded by different body weights maintained at Avian Research and Training Centre, University of Veterinary and Animal Sciences, Lahore. A total of 432 adult (12 weeks-old) quails, comprising 108 males and 324 females were randomly divided into 108 experimental units, comprising one male and three females each. These experimental units were randomly assigned to 12 treatment groups having 4 close-bred flocks x 3 female body weights (heavy 300-350g, medium 250-300g and small 200-250g) with randomized complete block design in factorial arrangements having 9 replicates in each treatment. Serum glucose, albumin, total protein, cholesterol and urea were studied. Mean serum glucose level in male and female quails was not significantly different among imported and local flocks. The total serum protein was significantly different in both the sexes, whereas, serum cholesterol and serum albumin levels were only significantly different in female quails of imported and local flocks. Serum urea concentration was only significantly (p<0.05) different in male quails. With respect to body size categories, all the biochemical parameters studied were not significantly different in both sexes of quails. The interaction between flocks and body size was significant (p<0.05) for serum protein and urea in both the sexes, only significant (p<0.05) in male quails for serum cholesterol and was only significant (p<0.05) in females for serum albumin.
Keywords: Blood serum chemistry values (Serum glucose; total protein; albumin; cholesterol and urea